(untitled) (Biological Sciences - PJSIR, 1996)
Studies were undertaken to assess physiological and comfort properties of sixdifferentjute-cotton union fabrics viz. Diamond, Twill, Ribbon, DW plain*, two types of Jeans (Jeans A and Jeans B) and five other commercially available cotton fabrics viz: Gueberdine, Poplin, Jeans (Jeans C), Khaddar (a local trade name) and Drill. Of all the samples, Jeans C showed highest value of thermal conductivity (l16.11mW/m°C) while Khaddar showed the lowest (5l.l1 mW/m°C). Jeans B showedhighest absorbency while Diamond showed lowest absorbency. In addition to previous eleven samples, five more samples of different materials were tested for generation of static charge. Jeans C, Markin and Mattress cover were found to generate lowest static charge (4.8 x 10-9coulornb/rn-) while polyester generated highest static charge (29.2 x 10.2 coulornb/m"). Drill had been found to have the best comfort properties in respect of thermal conductivity, water absorbency and static charge while Jeans A had the better comfort proper- ties among all the tested jute-cotton union fabrics. Microbiological examinations were carried out on two samples. Mycotoxin producing fungi and allergy producing fungi were not found in the samples.